CASSANDRA WEBB’S SEARCH FOR IDENTITY AND DEFENSE MECHANISMS IN MADAME WEB (2024) THROUGH FREUD’S PSYCHOANALYTIC THEORY - Mercuri Margareth Pah Mercuri Pah; Maya Sekartaji (DIALEKTIKA: JURNAL BAHASA, SASTRA DAN BUDAYA, 2025)
Abstract This study analyzes Cassandra Webb’s search for identity and defense mechanisms she employs in the film Madame Web (2024) through Sigmund Freud’s psychoanalytic theory. Focusing on the structure of the id, ego, and superego, the research examines how Cassandra unconscious conflict and anxieties shape her behaviour as she struggles to adapt to her sudden clairvoyant abilities and the responsibilities attached to them. Using a qualitative descriptive method, the study collects data from selected scenes, dialogues and character interactions that reveal Cassandra’s internal tension and coping strategies. These data are then interpreted using Freud’s concepts of personality structure and defense mechanisms. The findings show that Cassandra’s identity formation is closely tied to the dynamic interaction between her id’s instinctual impulses, her ego’s reality-based considerations, and her superego’s moral demands. Throughout the film, she frequently relies on defense mechanisms such as denial, rationalization, and projection to manage fear, guilt and overwhelming responsibility. These mechanisms both protect and delay her psychological growth until she gradually integrates her powers into a more coherent sense of self. Overall, the study demonstrates that Freud’s psychoanalytic framework remains effective for explaining the psychological depth of contemporary superhero characters and highlights how Madame Web (2024) portrays inner conflict and identity negotiation beyond its surface-level narrative. Keywords: Cassandra Webb; identity search; defense mechanisms; denial; rationalization; id, ego, superego; Madame Web (2024)